2024
DOI: 10.3390/nu16050624
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Its Influence on Anthropometric and Fitness Variables in High-Level Adolescent Athletes

Antonio E. Vélez-Alcázar,
Juan Alfonso García-Roca,
Raquel Vaquero-Cristóbal

Abstract: The objectives of the present research were to analyze adherence to the Mediterranean diet (AMD), to observe which variables most affect AMD, and to analyze whether AMD affects physical fitness and anthropometric parameters in high-level adolescent athletes. A total of 96 adolescent athletes in the under-16, under-18, and under-20 categories selected by the Athletics Federation of the Region of Murcia, of whom 47 were male (age = 18.31 ± 2.31 years old) and 49 female (age = 17.27 ± 1.44 years old), participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(96 reference statements)
2
0
0
Order By: Relevance
“…Regarding the differences in active adolescents with different levels of AMD, the results showed no significant differences in any of the study variables when comparing active adolescents with different levels of AMD. These results are in line with previous research in active adolescents in which AMD was not a determinant of the changes observed in kinanthropometric, body composition and fitness variables [ 58 , 66 ]. This could be due to the fact that in active adolescents diet is not as relevant to generate adaptations in anthropometric variables, body composition or physical condition because they compensate for possible deficits with regular physical activity [ 58 , 66 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the differences in active adolescents with different levels of AMD, the results showed no significant differences in any of the study variables when comparing active adolescents with different levels of AMD. These results are in line with previous research in active adolescents in which AMD was not a determinant of the changes observed in kinanthropometric, body composition and fitness variables [ 58 , 66 ]. This could be due to the fact that in active adolescents diet is not as relevant to generate adaptations in anthropometric variables, body composition or physical condition because they compensate for possible deficits with regular physical activity [ 58 , 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous research in active adolescents in which AMD was not a determinant of the changes observed in kinanthropometric, body composition and fitness variables [ 58 , 66 ]. This could be due to the fact that in active adolescents diet is not as relevant to generate adaptations in anthropometric variables, body composition or physical condition because they compensate for possible deficits with regular physical activity [ 58 , 66 ]. Therefore, AMD could play a relevant role, but always accompanied by other physical activity or fitness variables.…”
Section: Discussionsupporting
confidence: 93%